Dioxido{4,4′,6,6′-tetrabromo-2,2′-[2,2-dimethylpropane-1,3-diylbis(nitrilomethanylylidene)]diphenolato}molybdenum(VI) - Kargar, Hadi (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, [Mo(C(19)H(16)Br(4)N(2)O(2))O(2)], comprises two molecules. The coordination environments around the Mo(VI) atoms are distorted octahedral, defined by two oxide ligands and an N(2)O(2) donor set of the tetradentate Schiff base in each molecule. The dihedral angles between the benzene rings in the molecules are 76.2 (3) and 77.7 (3)°. An interesting feature of the crystal structure is the presence of Br⋯Br contacts [3.4407 (11), 3.5430 (11) and 3.6492 (10) Å], which are shorter than the sum of the van der Waals radius of Br atoms (3.70 Å). The crystal structure is further stabilized by intermolcular C—H⋯Br and C—H⋯π interactions. The crystal under investigation was twinned by nonmerohedry in a 0.053 (1):0.947 (1) ratio.